2020
DOI: 10.1504/ijsem.2020.107794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of service quality, self-service technology, and the corporate image on customer satisfaction and customer revisit intention among luxury hotels in Kuala Lumpur, Malaysia

Abstract: According to World Travel & Tourism Council, the tourism industry in Malaysia has been boomed prosperously in few years. Accordingly, such phenomenon has largely propelled the competition in hospitality industry, especially the race between service-oriented hotels and luxury hotels. Nevertheless, numerous issues associated with customer satisfaction have been reflected on hotel booking website, which is worth studying in depth, as it is more likely to adversely affect profitability and competitiveness of luxur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
2
8
0
Order By: Relevance
“…However, as noted by the research [35], we also found that IT application usage to ensure food service quality has no direct impact on the revisit intention. This is in line with the findings of the research [70], who posited that in the hotel industry, IT application usage to ensure food service quality has little influence on the revisit intention.…”
Section: Reliability Testsupporting
confidence: 52%
See 1 more Smart Citation
“…However, as noted by the research [35], we also found that IT application usage to ensure food service quality has no direct impact on the revisit intention. This is in line with the findings of the research [70], who posited that in the hotel industry, IT application usage to ensure food service quality has little influence on the revisit intention.…”
Section: Reliability Testsupporting
confidence: 52%
“…Although, as noted by Li et al [35,26], the hotel industry is slowly adopting technology, they found that the property management system (PMS) is the most important IT application in the hotel industry, followed by the "points of sales" (POS) and the "central reservation system" (CRS). They demonstrated the IT application's significance and importance in the hotel industry.…”
Section: Information Technology In Food Service Qualitymentioning
confidence: 99%
“…Some researchers have attempted to evaluate customers' choice of choosing SSTs through the cognitive, demographic, and situational determinants [40,45]. SSTs' impact on the customer satisfaction has been studied [37,46,47]; however, understanding factors that bring about service excellence by adopting SSTs in tourism has not received deserved attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2. The most used age group for electronic retail trade was between (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at a rate of % 55 while the age group (40 and above) was the least used as it reached 9.8 %, which means that electronic retail trade sites target their products and services to the youth category with more attention than the rest of the categories Other ages target its goods and services. 3.…”
Section: Resultsmentioning
confidence: 99%
“…It manner that they are able to do buying the way they prefer and in line with their choice. while doing buying online, the customer can concurrently do different important activities like cooking food, watching TV, discussing with circle of relatives members, etc [19,20]. Eretailing design and development perspective structure is presented in the Figure 1.…”
Section: Introductionmentioning
confidence: 99%